Patient Characteristics in Oral Cancer Staging - Hoffman, Matthew J.; Hale, Demetria D.; Hale, Elijah W. (Frontiers in Oral Health, 2022)
Background: Early detection of oral cancer is an important goal for oral healthcare providers, as survival rates for oral cancers diagnosed at an advanced stage are less than half the rates for cancers diagnosed in early stages. As many patients are asymptomatic in early stages, it is crucial for oral healthcare providers to have a high index of suspicion while treating patients at risk for late diagnosis. Objectives: To identify characteristics associated with each stage diagnosis of oral cancer Methods: We performed a retrospective chart review using the TriNetX database. We identified two cohorts of interest: patients with an initial diagnosis of stage 1 oral cancer, and patients with an initial diagnosis of stage 3 or 4 oral cancer. Statistical comparison of cohort characteristics was completed through the TriNetX statistical software platform. Results: We identified 386 patients diagnosed at stage 1 and 869 patients diagnosed at stage 3 or 4. We identified several characteristics not previously reported in the literature. Race, BMI between 20-29, malnurition, anemia were all associated with late stage diagnosis. Certain medications were also associated with late stage diagnosis, such as heparin derivatives and diclofenac. Our findings also reinforced prior research for characteristics such as nicotine use and ethnicity. Conclusions: Our findings offer new characteristics that may aid oral healthcare providers in detecting oral cancer at an early stage. Increasing provider awareness of factors that they may not have considered previously could increase the rates of early stage cancer detection, improving overall patient mortality and curative outcomes.